How maternal exposure to aflatoxin B1 impacts the development of progeny intestinal immune system? - Bastos-Amador, P. (2021)
Abstract publicado em: Abstracts / Toxicology Letters 350S (2021) S245–S246. https://www.eurotox2021.com/wp-content/uploads/EuroTox-2021-Final-abstract-book-by-Elsevier.pdf